1999
DOI: 10.4141/a98-121
|View full text |Cite
|
Sign up to set email alerts
|

A study of growth and carcass traits in dehorned and polled composite bulls

Abstract: . 1999. A study of growth and carcass traits in dehorned and polled composite bulls. Can. J. Anim. Sci. 79: 383-385. Phenotypically dehorned (genetically horned) and polled bulls were similar for birth, weaning weight, pre-and post-weaning ADG, carcass weight, grade fat, marbling, rib-eye area, cutability and carcass grade. Polled bulls had higher (P < 0.02) fat over the rib-eye compared with dehorned. The similarity in growth and a majority of carcass traits between polled and horned, would suggest that breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
2
2
0
1
Order By: Relevance
“…These findings were recently confirmed by own evaluations based on the database from the German national genetic evaluation for Holstein AI sires [ 26 ]. Quite similar results were reported for dual-purpose German Simmental cattle, while no differences between polled and horned groups were found with regard to health, growth and reproductive traits in beef cattle [ 10 , 27 – 29 ]. Evidence accumulated for polled German Simmental cattle, as well as more recent advances in the Holstein breed, further indicate that the initial inferior performance of polled individuals might be due to a selection advantage of their horned pendants rather than an inevitable genetic disadvantage [ 22 , 30 ].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings were recently confirmed by own evaluations based on the database from the German national genetic evaluation for Holstein AI sires [ 26 ]. Quite similar results were reported for dual-purpose German Simmental cattle, while no differences between polled and horned groups were found with regard to health, growth and reproductive traits in beef cattle [ 10 , 27 – 29 ]. Evidence accumulated for polled German Simmental cattle, as well as more recent advances in the Holstein breed, further indicate that the initial inferior performance of polled individuals might be due to a selection advantage of their horned pendants rather than an inevitable genetic disadvantage [ 22 , 30 ].…”
Section: Introductionsupporting
confidence: 76%
“…Hence, the urgent need for alternatives to cattle dehorning is strengthened. Simply avoiding dehorning by keeping naturally-horned cattle is considered as one possibility [ 8 ], but implies substantial adaptation of housing conditions and does not contribute to reduce the risk of injuries among cattle and animal keepers [ 9 , 10 ]. In this regard, targeted selection and dissemination of genetically-polled animals into naturally-horned cattle breeds (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that as the accuracy of EBVs increased to 70%, many of the significance differences were not sustained. The results are consistent with previous research on the impact of polledness on beef productivity of different breeds of cattle [ 5 , 14 , 16 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Genetic effects due to inbreeding have been noticed in dairy cattle because of a few polled elite bulls used through artificial insemination [ 12 , 13 ]. On the other hand, perceptions about the undesirable effects of polledness on beef production have been largely annulled by comparing different traits of growth, carcass yield, and meat quality in a few beef breeds and cross-bred herds [ 5 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Keunggulan dari sifat tanpa tanduk, yakni generasi homozigot pada sapi tanpa tanduk mengurangi biaya dan waktu untuk pemotongan tanduk dan menghilangkan stres pada ternak (Medugorac et al, 2012;Prayaga 2007;Zulkharnain et al, 2017). Beberapa keunggulan lain pada sapi tanpa tanduk dari segi manajemen pemeliharaan, seperti mengurangi resiko terluka yang sering terjadi pada ternak yang disebabkan oleh tanduk, dapat mencegah memar dan kerusakan pada kulit (Goonewardene et al, 1999). Seleksi terhadap sapi tanpa tanduk sangat penting terutama pada manajemen budidaya ternak modern (Zulkharnaim et al, 2020).…”
Section: Pendahuluanunclassified